Risk versus risk: a review of benzodiazepine reduction in older adults. (July 2014) - Paquin, Allison M; Zimmerman, Kristin; Rudolph, James L
Abstract : Introduction: Benzodiazepines (BZD) are potentially inappropriate for older adults, yet their use persists. Patients and providers may hesitate to discontinue BZDs due to concerns for withdrawal or relapse. We reviewed the literature for BZD reduction protocols to examine common elements, safety and efficacy. A framework is proposed for clinicians to address BZD reduction challenges. Areas covered: Following a systematic literature review, this analysis included 28 studies of older out-patients tapering chronic BZDs. Populations included insomnia, depression and anxiety. Protocols included taper alone (32%), taper plus cognitive behavioral therapy (32%) and taper plus medication substitution (36%). Success rates were favorable for all modalities (mean 60%, median 67%, range 25 – 85%) and independent of dose or duration of use. Common schedules included a 25% dose reduction over 1 – 2 weeks until drug-free. Withdrawal symptoms included mainly mild psychological and somatic concerns. No serious safety events were reported. Expert opinion: BZD reduction protocols among older adults are feasible and successful. Given unique cognitive and functional abilities and comorbidities of older adults, a patient-centered approach to reduction is needed. Our framework guides clinicians in planning and persisting with BZD reduction, while our checklist addresses tailored tapers. Monitoring and support is emphasized, and taper modifications are proposed for struggling patients.